PERSEPSI GURU TERHADAP IMPLEMENTASI KURIKULUM MERDEKA DI SMP NEGERI 5 PARIAMAN - Mellisa F; Irvan Beatres (Ensiklopedia Education Review, 2026)
This research is based on the fact that many teachers experience difficulties in implementing the independent curriculum, which involves more interaction with IT (Information and Technology), so teachers who are not proficient in operating it face difficulties and lag behind in implementing the independent curriculum. Additionally, in the learning process, school facilities such as LCD projectors and laptops are not yet adequate, which contradicts the implementation of the independent curriculum that involves more interaction with IT (Information and Technology), and the learning books are not suitable for students' needs. The purpose of this study is to understand teachers' perceptions of the implementation of the Independent Curriculum at SMP Negeri 5 Pariaman, as well as to identify the obstacles faced. . This type of research is qualitative descriptive research. The research informants are all teachers in the school, selected using purposive sampling techniques. The data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing or verification. The data analysis technique uses triangulation. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions or verification. The data analysis technique used triangulation. Based on the research results, it was found that the teachers have a good understanding and positive experience of the Merdeka Curriculum. They see it as a flexible, student-centered approach that encourages creativity. However, there are several challenges faced by teachers, such as limited access to the internet and digital devices, lack of textbooks, minimal formal training, as well as personal difficulties in understanding the concepts and applications of the Merdeka Curriculum, including the use of the Merdeka Mengajar Platform (PMM). Nevertheless, teachers demonstrate high initiative and adaptability in overcoming these obstacles, through self-learning, collaboration in MGMP, and utilizing available resources.Keywords: Teacher Perception, Merdeka Curriculum, Obstacles